Deep-Sea Bacteria: Growth and Utilization of Hydrocarbons at Ambient and In Situ Pressure - Schwarz, J. R. (1974)
Microorganisms present in Atlantic Ocean sediment samples collected at a depth of 4,940 m were found to be capable of utilizing hydrocarbons under both ambient and in situ pressures. The rate of utilization under in situ pressure (500 atm) and ambient temperature (20 C) was found to be significantly less compared with hydrocarbon utilization examined under conditions of ambient temperature (20 C) and pressure (1 atm).